2013
DOI: 10.1155/2013/541679
|View full text |Cite
|
Sign up to set email alerts
|

Syringocystadenoma Papilliferum of the Bony External Auditory Canal: A Rare Tumor in a Rare Location

Abstract: Tumors originating from ceruminous glands are rare lesions of the external auditory canal. The lack of specific clinical and radiological signs makes their diagnosis challenging. We report the case of an exceptionally rare benign tumor, a syringocystadenoma papilliferum (SCAP), in an atypical location in the bony segment of the external auditory canal with uncommon clinical signs. The special traits of the case included the following: the most lateral component of the tumor was macroscopically cystic and a gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 12 publications
(19 reference statements)
0
16
0
Order By: Relevance
“…Adding our case to those already published, there are little more than a dozen cases of syringocystadenoma papilliferum reported in the literature [6]. …”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Adding our case to those already published, there are little more than a dozen cases of syringocystadenoma papilliferum reported in the literature [6]. …”
Section: Introductionmentioning
confidence: 75%
“…In this case report we describe the clinical manifestation and histological features of one of the many varieties of ceruminous syringocystadenoma papilliferum described in the literature [ 6 ]. Adding our case to those already published, there are little more than a dozen cases of syringocystadenoma papilliferum reported in the literature [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ceruminous glands are modified sudoral glands, localized deep in the skin of the EAC [[5], [6], [7]]. Tumors of these glands, commonly grouped under the name « ceruminoma », are rare, and comprise 5% of EAC tumors [[8], [9], [10]]. These tumors can usually be divided into benign (such as: adenoma; pleomorphicadenoma; syringocystadenoma …) and malignant tumors (for example: adenoidcystic and mucoepidermoid carcinoma; adenocarcinoma) [5,8,11].…”
Section: Discussionmentioning
confidence: 99%
“…To my knowledge, only one study has demonstrated the case of a patient with SCAP arising from the bony part of the canal [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Eleven cases of SCAP of the cartilaginous par0000t of the external auditory canal have been mentioned in the literature till 2006 [5] . To my knowledge, another two cases have been mentioned since that time: one associated with lipomatous apocrine adenomas [6] and the other originating from the bony part of the ear canal [7] .…”
Section: Introductionmentioning
confidence: 95%